MiR-145 on the Proliferation of Ovarian Cancer Cells by Regulating the Expression of MMP-2/MMP-9 - Wang, Mei; Zhang, Shu (Cellular and Molecular Biology, 2022)
This study aimed to consider the effect of miR-145 on the proliferation of OC cells by regulating the expression of MMP-2/MMP-9. In this experiment, the miR-145 target gene with restriction enzyme cut sites was amplified from the four groups of rat genomes, and it was ligated to the pIRES plasmid to form a recombinant plasmid and identified. The miR-145 recombinant plasmid and the empty plasmid into OC cells were transfected, and qRT-PCR was used to detect the expression of miR-145 in the transfected OC cells. Experimental data showed that there are a total of 60 healthy male SD rats, randomly divided into 4 groups, namely the normal saline control group (group A), the model group ( group B), treatment group with 30 mg miR-145 (group C), and treatment group with 100mg miR -145 (group D). The experimental results showed that compared with group A, the expression of MMP-2 protein in rats in groups B, C, and D all increased to varying degrees on 7 days, 14 days, and 28 days, reaching the highest at 14 days. This study shows that miRNA-145 is under-expressed in OC cell lines, and miR-145 can significantly inhibit the proliferation and invasion of ovarian cells by regulating the expression of MMP-2/MMP-9.